2010
DOI: 10.1139/tcsme-2010-0015
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Effects of the Interference Fit of Motor Rotor on the Stiffness of a High Speed Rotating Shaft

Abstract: Developing a motor-built-in high speed spindle is an important key technology for domestic precision manufacturing industry. The dynamic analysis of the rotating shaft is the major issue in the analysis for a motor-built-in high speed spindle. One of the major concerns is how the motor rotor is mounted on the shaft, by interference (shrink) fit or else. In this study, dynamical analyses are carried out on a motor-built-in high speed spindle. The motor rotor is mounted on the spindle shaft by means of interfere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 13 publications
(11 reference statements)
0
5
0
Order By: Relevance
“…The detailed derivations can be referred in [18]. With zero initial conditions, the displacement response evaluated in frequency domain is expressed as Fig.…”
Section: M€ X X(t)zkx(t)~f(t) ð2þmentioning
confidence: 99%
See 2 more Smart Citations
“…The detailed derivations can be referred in [18]. With zero initial conditions, the displacement response evaluated in frequency domain is expressed as Fig.…”
Section: M€ X X(t)zkx(t)~f(t) ð2þmentioning
confidence: 99%
“…The accuracy of the results was yet to be verified. Chen [16][17][18] indicated that the overall stiffness of a spindle was considerably influenced by the fitted rotor. The natural frequencies tend to increase with the rotor mounted on the shaft by interference fit.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of calculation and analysis provide theoretical basis and data for the optimal design and control of the motor. [18][19][20] The structure of motor…”
Section: Introductionmentioning
confidence: 99%
“…General FE contact problems are discussed in Zhang and Wang, 6 where translational joint contact with friction force is studied in 2D, and in Nejati et al, 7 where internal friction of contact on a cracked region is studied. Many publications that consider the use of traditional beam or similar 1D elements such as Santos et al 8 and Chen et al 9 typically present a casedependent solution for shrink-fitted sleeve-shaft contact. The solution is mainly about tuning the sleeve material properties, as based on the theory developed.…”
Section: Introductionmentioning
confidence: 99%